ANALISIS IMPLEMENTASI PROGRAM KEWIRAUSAHAAN DALAM MENGEMBANGKAN STRATEGI PEMASARAN 4P MELALUI MAGANG MANDIRI DI PKBM NURUL ISLAM - Zulliansyah Prawira Kuswara; Safuri Musa; Dayat Hidayat (Comm-Edu (Community Education Journal), 2026)
The Independent Internship Program at Universitas Singaperbangsa Karawang, conducted at PKBM Nurul Islam, is part of a government initiative to foster self-reliance and economic empowerment among learners through a three-month entrepreneurship program. This study aims to analyze the implementation of the entrepreneurship program in developing 4P marketing strategies within the independent internship framework. A descriptive qualitative approach was employed, involving PKBM administrators, entrepreneurship tutors, and learners as subjects. Data were collected through interviews, observations, and documentation, and subsequently analyzed using data reduction, data presentation, and conclusion drawing. The results indicate that the program—executed through planning, implementation, and evaluation phases—successfully enhanced the participants' basic understanding of 4P marketing strategies. However, implementation still faced challenges regarding product packaging, pricing, distribution, and digital promotion. The study recommends strengthening entrepreneurship education to make it more practical and offers a novel contribution by examining the implementation of 4P marketing strategies through independent internships within the PKBM setting.